DIABETES SELF MANAGEMENT EDUCATION (DSME) DENGAN KETIDAKSTABILAN KADAR GLUKOSA DARAH PADA PENDERITA DIABETES MELITUS - Maria, Insana (School of Nursing, Faculty of Medicine and Health Science, Universitas Lambung Mangkurat, 2019)
Background: Diabetes mellitus is a disease that is incurable, nursing management of patientswith diabetes mellitus can be done by nurses to give diabetes self-management education(DSME). DSME gives highly influential instability to blood glucose levels, one of them instabilityin blood glucose levels in people with diabetes mellitus. Purpose: To understand the relationshipbetween Diabetes Individual Diabetes Education (DSME) and Unstable Blood Glucose Levels inDiabetes Mellitus Patients. Method: The method used in this research is the analytical methodwith the correlation search design and the porpusive sampling technique with the totalpopulation 318 people and the sample number 177 people. The analysis is presented in the formof a frequency distribution table. Result: From the result of spearman (rho), p = 0.414 <α (0.05)pre and p = 0.417 <α (0.05) post which means that H0 is rejected and Ha accepted, by whichthere is a relationship between Diabetes Self Management Education DSME) With unstable bloodglucose levels in patients with diabetes mellitus. Recommendation: It is expected that thisresearch could be used as a source of information in carrying out complementary actions toreduce the blood glucose level in non-pharmacological diabetes mellitus by providing knowledgeabout self-management education of diabetes (DSME).